2005
DOI: 10.1111/j.1742-7843.2005.pto_146.x
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Homocysteine in Elderly with Heart Failure Improved Vascular Function and Blood Pressure Control but did Not Affect Inflammatory Activity

Abstract: Abstract:We have previously shown that hyperhomocysteinaemia is common in elderly heart failure patients, and is associated with endothelial dysfunction, impaired vasodilatory capacity and a low-grade inflammation. In the present study we examined if supplementation with B 6 , B 12 and folate could normalize the hyperhomocysteinaemia and if so, in turn, would improve the associated parameters. This was an open study without placebo control on heart failure patients with plasma homocysteine Ͼ 15 mM. Measurement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 18 publications
1
20
0
1
Order By: Relevance
“…Some studies have proposed a mechanism whereby a high homocysteine level could cause heart failure. Additionally, some studies have reported that vitamin supplementation, including folic acid supplementation, improved the potency of vasodilation and decreased blood pressure, 32,33) whereas others have suggested that such supplements are not effective. 6,34,35) Therefore, in addition to evaluating the long-term outcome of the subjects in this study, further studies on the possible benefits of vitamin supplementation are necessary.…”
Section: Limitationsmentioning
confidence: 99%
“…Some studies have proposed a mechanism whereby a high homocysteine level could cause heart failure. Additionally, some studies have reported that vitamin supplementation, including folic acid supplementation, improved the potency of vasodilation and decreased blood pressure, 32,33) whereas others have suggested that such supplements are not effective. 6,34,35) Therefore, in addition to evaluating the long-term outcome of the subjects in this study, further studies on the possible benefits of vitamin supplementation are necessary.…”
Section: Limitationsmentioning
confidence: 99%
“…(2) Smoking may severely affect the cutaneous responses, however we excluded such subjects in this study [4]. (3) Degree of inflammation in the vasculature may be a confounder and we have earlier published that homocysteine, CRP and cytokines could be a marker of heart failure [9]. The present subjects had several markers of inflammation that differed between the two groups of heart failure (Table 3).…”
Section: Discussionmentioning
confidence: 93%
“…Interestingly, both heart failure groups had attenuated responses to ACh, SNP and heat as compared to that seen in the healthy controls. If anything, the reductions were more pronounced in the mild NYHA II group as compared to the severe heart failure group which may argue against a purely causative role of inflammation in diminished vasorelaxant reactivity [9]. and (4) Other clinical parameters such as plasma sodium and potassium were within acceptable values and can thus not be confounders.…”
Section: Discussionmentioning
confidence: 94%
“…A similar strategy of combining B vitamins to reduce homocysteine in patients with CCF increased vasodilatory capacity, and reduced MAP but did not affect inflammatory markers [89]. No long term data are available for CCF patients.…”
Section: Vitamin B 12mentioning
confidence: 97%
“…Patients with CCF have low intakes of folate [10], and around 10% of patients with heart failure have folate deficiency [84]. The adverse vascular effects of folate deficiency are mediated only in part through hyperhomocysteinaemia [85], and supplementation in CCF patients might include improved endothelial function [86] with consequent improvements in autonomic function.…”
Section: Folatementioning
confidence: 97%